When Psychosis Meets Chorea: Multidisciplinary Diagnosis of Suspected Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections in a Pre-adolescent Girl - Ayu Putri Satyawati; Komang Yasmika Utami; I Made Ananta Wijaya (The International Journal of Medical Science and Health Research, 2025)
Background Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal Infections (PANDAS) are characterized by the abrupt onset of neuropsychiatric symptoms temporally linked to Group A β-hemolytic Streptococcus infection. The condition remains diagnostically challenging due to overlapping features with other autoimmune and psychiatric disorders, absence of definitive biomarkers, and variable infectious histories. Objective To describe a diagnostically complex case of PANDAS in a preadolescent girl presenting with concurrent choreiform movements, acute psychosis, and subclinical valvular changes. Case A 12-year-6-month-old previously healthy girl developed sudden-onset involuntary dance-like movements and acute psychiatric symptoms, including auditory hallucinations and bizarre delusions. Neurological examination revealed chorea without focal deficits. Echocardiography showed mild mitral and tricuspid regurgitation. Anti Streptolysin O (ASTO) test was positive, but other Laboratory markers of inflammation were normal. The temporal clustering of symptoms, subtle cardiac findings, positive ASTO test and exclusion of alternative diagnoses supported a working diagnosis of PANDAS. Management included antipsychotic, benzodiazepine, and anticonvulsant therapy, with referral for tertiary evaluation and potential immunomodulation. Conclusion This case emphasizes the importance of early recognition of PANDAS in children with abrupt neuropsychiatric and motor symptom onset, the necessity of thorough differential diagnosis, and the value of multidisciplinary care in optimizing outcomes.